Associations between grain intake and hospitalized nephrolithiasis in Chinese adults: a case-control study. Issue 8 (4th April 2023) - Shan, Liping; Shi, Jianxiu; Li, Jia; Pan, Chunyu; Xia, Yang; Niu, Kaijun; Li, Zhenhua; Bai, Song
Abstract : Nephrolithiasis is one of the most common urological disorders. Abstract : Introduction : nephrolithiasis is one of the most common urological disorders. Grains are essential staple foods worldwide. This study aimed to investigate the associations between whole grains and refined grains intake, and hospitalized nephrolithiasis in a Chinese population. Methods : the patients and healthy participants were enrolled in the Shenyang sub-cohort of Tianjin Chronic Low-Grade Systemic Inflammation and Health Cohort Study. After selecting and matching by age (±one year) and sex using a 1 : 2 ratio, a total of 666 participants (222 patients and 444 healthy controls) were included. Whole grains and refined grains intake was measured using a validated self-administered food frequency questionnaire. Multivariate conditional logistic regression analysis was used to evaluate the associations between whole grains and refined grains intake with hospitalized nephrolithiasis. Results : after multivariable adjustments, a higher intake of whole grains was inversely associated with hospitalized nephrolithiasis. Compared to participants with the lowest tertile of whole grains intake, the adjusted odds ratio (OR) and 95% confidence interval (CI) of hospitalized nephrolithiasis for participants in the highest tertile was 0.58 (0.26, 0.81) ( P for trend = 0.020). In contrast, a higher intake of refined grains was positively associated with nephrolithiasis. Compared to participants with the lowest tertile of refined grains intake, the adjusted OR (95% CI) of hospitalized nephrolithiasis for participants in the highest tertile was 3.75 (1.48, 9.52) ( P for trend = 0.006). The results were consistent in both genders. Conclusion : the consumption of whole grains was found to be negatively associated with hospitalized nephrolithiasis, while the consumption of refined grains was positively associated with hospitalized nephrolithiasis. Therefore, a substitution of whole grains for refined grains consumption may assist in hospitalized nephrolithiasis prevention.